Measurement of CP violation in the phase space of B± → K±π+π− and B± → K±K+K− decays - Aaij, Roel; Aquines Gutiérrez, Osvaldo; Bachmann, Sebastian; Bien, Alexander; Blouw, Johan; Britsch, Markward; Di Canto, Angelo; Dordei, Francesca; Färber, Christian; Fontana, Marianna; Gersabeck, Evelina; Grünberg, Oliver; et al. (Physical review letters, 2013)
The charmless decays B±→K±π+π− and B±→K±K+K− are reconstructed using data, corresponding to an integrated luminosity of 1.0 fb−1, collected by LHCb in 2011. The inclusive charge asymmetries of these modes are measured as ACP(B±→K±π+π−)=0.032±0.008 (stat)±0.004 (syst)±0.007(J/ψK±) and ACP(B±→K±K+K−)=−0.043±0.009 (stat)±0.003 (syst)±0.007(J/ψK±), where the third uncertainty is due to the CP asymmetry of the B±→J/ψK± reference mode. The significance of ACP(B±→K±K+K−) exceeds three standard deviations and is the first evidence of an inclusive CP asymmetry in charmless three-body B decays. In addition to the inclusive CP asymmetries, larger asymmetries are observed in localized regions of phase space.
Im Titel sind "±", "+" und "-" hochgestellt
LHCb Collaboration: R. Aaij, O. Aquines Gutierrez, S. Bachmann, A. Bien, J. Blouw, M. Britsch, A. Di Canto, F. Dordei, C. Färber, M. Fontana, E. Gersabeck, O. Grünberg, S. Hansmann-Menzemer, T. Hartmann, A. Jaeger, K. Kreplin, G. Krocker, B. Leverington, C. Linn, J. Marks, M. Meissner, T. Nikodem, D. Popov, M. Schmelling, P. Seyfert, S. Stahl, J. van Tilburg, U. Uwer, D. Volyanskyy, C. Voß, H. Voss, R. Waldi, S. Wandernoth, D. Wiedner, M. Zavertyaev, A. Zhelezov und weitere 613
Gesehen am 22.04.2021